Bacterial Analysis of Selected Drinking Water Sources in Mbarara Municipality, Uganda - Lukubye, Ben; Andama, Morgan (Journal of Water Resource and Protection, 2017)
Surveillance of water quality to ensure microbiological safety is a vital public health function to prevent water borne diseases. Bacterial total coliform and Escherichia coli (E. coli) examination provide indication of the hygienic condition of drinking water and are major tools in the assessment of the health risk borne by pathogen in water. Unfortunately, there is insufficient information on the total coliform and E. coli amounts in the common drinking water sources in Mbarara Municipality, Uganda despite the eminent anthropogenic sources of contamination. Hence the study established the sanitary risk and quantified the total coliform and E. coli load in selected drinking water sources in Mbarara Municipality, Uganda. A total of 70 water samples were collected from selected boreholes, springs, wells and rainwater in Nyamitanga, Kamukuzi and Kakoba divisions of Mbarara municipality. The water samples were analysed for total coliform and E. coli abundance using the American Public Health Association (APHA) standard method. The total coliform and Escherichia coli counts were compared with the World Health Organization (WHO) drinking water standard guidelines. The findings indicate that all the studied groundwater sources (boreholes, springs and wells) in Mbarara Municipality were not compliant to either both or one of the WHO total coliform (<10 CFU/100 ml) and E. coli (0 CFU/100 ml) criteria for drinking water hence they are unsuitable for drinking without treatment e.g. boiling etc. Only rainwater collected from Mbarara University of Science and Technology met the WHO total coliform and E. coli criteria for drinking water thus is suitable for drinking without any treatment. There is a strong linkage between bacterial (total coliforms and E. coli) water quality and water source sanitation, as well as the proximity of latrines, animal farms and landfills around the water sources. Mbarara municipal council should therefore ensure effective and regular operation and maintenance of the drinking water sources through the adoption and promotion of appropriate water safety plans.